PERAN KIAI HAJI IRFAN HIELMY DALAM MENGEMBANGKAN DUNIA PENDIDIKAN DAN DAKWAH DI KABUPATEN CIAMIS JAWA BARAT (1933-2010) - Nurhasanah, Elah (Prodi PAI IAILM Suryalaya, 2018)
The development of Islam specifically in the world of da'wahand education in the Ciamis area is inseparable from the role of the kiaior community leaders in the area. One of the figures of many kiai isKiai Haji Irfan Hielmy, who is supported in Dewasari Village,Dewasari Village, Cijeungjing District, Ciamis Regency, West Java.Seeing so the contribution of Irfan Hielmy to the development of Islamin Ciamis, then there was an interest in studying the figure as one of thelinks in the development of Islam in Indonesia specifically in the field ofIslamic education and propaganda. In the world of education, IrfanHielmy always asks his students to study anywhere in order to havebroad insights. Making his students as moderate Muslims, democraticbelievers, and diplomatic muhsin. His da'wah activity is theimplementation of amar ma'ruf nahi munkar. Irfan Hielmy which isapplied to the students and the community in Ciamis Regency, has agreat influence on people's lives. His da'wah activity is theimplementation of amar ma'ruf nahi munkar